Toward seamless environments for dispute prevention and resolution - Carneiro, Davide Rua (2011)
Given the evolution of the Information Technology society, it is now rather simple to acquire products or services in a foreign country. This practice may conduct to the event of conflicts whenever a consumer detects some fault or malfunction in services or products he/she had bought. A situation that may worsen if at the time of the uncovering of the defect, the shopper is already in a different geographical arena. There is thus the need to develop computational tools that may prevent these disputes from even happening. In this work it is proposed the development of seamless intelligent environments for dispute resolution that will surround the user, independently of his/her location. It is described the implementation of a prototype that may provide contextualized real-time information and legal support to consumers. The objective is to decrease the number of disputes due to a poor understanding in relation to the The Law and make justice more personalized and closer to people.